Organ-specific small protein networks in 100 kDa ultrafiltrates: functional analysis and implications for neuroregenerative medicine - Slivka, Jakub Peter; Bauer, Chris; Halhouli, Tasneem; Younsi, Alexander; Wong, Michelle B. F.; Chan, Mike K. S.; Skutella, Thomas (International journal of molecular sciences, 2025)
In this research, the proteomic landscape of 100 kDa protein extract sourced from rabbit brain was compared to extracts from liver and from organ mixture (OM). Our aim was to compare the efficacy of Nanomised Organo Peptides (NOP) ultrafiltrates from two different tissues and a tissue mixture for inducing neurite outgrowth, and subsequently to identify the molecular networks and proteins that could explain such effects. Proteins were isolated by gentle homogenization followed by crossflow ultrafiltration. Proteomic evaluation involved gel electrophoresis, complemented by mass spectrometry and bioinformatics. GO (Gene Ontology) and protein analysis of the mass spectrometry results identified a diverse array of proteins involved in critical specific biological functions, including neuronal development, regulation of growth, immune response, and lipid and metal binding. Data from this study are accessible from the ProteomeXchange repository (identifier PXD051701). Our findings highlight the presence of small proteins that play key roles in metabolic processes and biosynthetic modulation. In vitro outgrowth experiments with neural stem cells (NSCs) showed that 100 kDa protein extracts from the brain resulted in a greater increase in neurite length compared to the liver and organ mixture extracts. The protein networks identified in the NOP ultrafiltrates may significantly improve biological therapeutic strategies related to neural differentiation and outgrowth. This comprehensive proteomic analysis of 100 kDa ultrafiltrates revealed a diverse array of proteins involved in key biological processes, such as neuronal development, metabolic regulation, and immune response. Brain-specific extracts demonstrated the capacity to promote neurite outgrowth in NSCs, suggesting potential application for neuroregenerative therapies. Our findings highlight the potential of small proteins and organ-specific proteins in the development of novel targeted treatments for various diseases, particularly those related to neurodegeneration and aging.